2021
DOI: 10.1080/0886022x.2021.1922442
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular water/total body water ratio as predictor of mortality in hemodialysis patients

Abstract: Background: Overhydration is a predictor of mortality in hemodialysis (HD) patients. Bioimpedance spectroscopy (BIS) is used to determine the body composition. Extracellular Water/Total Body Water (ECW/TBW) ratio has been proposed to predict mortality. Methods: Multicenter, prospective, observational, proof-of-concept study to estimate the impact of ECW/TBW in global and cardiovascular mortality and the relationship with cardiovascular biomarkers. The study included 60 patients (mean age, 71.8 ± 11.4 years; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
0
19
0
2
Order By: Relevance
“…On the other hand, some previous studies reported that ECF/TBW ratio was a maker of the fluid volume status and was sometimes used to set dry weight in HD patients 19 , 20 . Recently, Kim et al 21 and Pérez-Morales et al 22 have demonstrated that volume overload assessed by BIA-measured ECF/TBW ratio was a predictor of all-cause and cardiovascular mortality. However, Kim et al 5 previously reported that ECF/ICF ratio but not ECF/TBW ratio was an independent predictor of all-cause and cardiovascular event.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some previous studies reported that ECF/TBW ratio was a maker of the fluid volume status and was sometimes used to set dry weight in HD patients 19 , 20 . Recently, Kim et al 21 and Pérez-Morales et al 22 have demonstrated that volume overload assessed by BIA-measured ECF/TBW ratio was a predictor of all-cause and cardiovascular mortality. However, Kim et al 5 previously reported that ECF/ICF ratio but not ECF/TBW ratio was an independent predictor of all-cause and cardiovascular event.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences were also observed in fat mass ( p = 0.01), fat-free mass ( p = 0.007), resting metabolic rate (RMR) ( p = 0.007), total body water ( p = 0.01) and extracellular water ( p = 0.004) between the groups [ 30 ]. In another study, the influence of ECW/TBW and cardiovascular mortality and the connection with cardiac biomarkers in hemodialysis patients was explored [ 31 ]. The study included 60 participants, 28 of whom died during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…A relação AEC/ACT ajustada é um índice validado que tem sido associado à sobrevida 15 . Nongnuch et al 16 consideraram dois desvios padrão de AEC/ ACT pós-diálise para definir o excesso de fluido (≥ 0,41) e outros autores encontraram significância em relações ≥ 0,47 17 .…”
Section: Antecedentesunclassified
“…Perez-Morales et al 17 publicaram recentemente um estudo de prova de conceito que constatou que a AEC/ACT ≥ 0,47 está associada a maior risco de mortalidade usando a análise da curva ROC. No presente estudo, a AEC/ACT ≥ 0,47 foi também o valor de corte com melhor sensibilidade e especificidade para predizer mortalidade durante o acompanhamento.…”
Section: Excesso De Fluidos Pressão Arterial E Mortalidadeunclassified